Utilizing vaginal natural orifice to facilitate bowel manipulation during totally intracorporeal ileal conduit construction: a retrospective cohort study - Kaipeng Jia; Shiwang Huang; Zhun Wang; Yuda Lin; Yiduo Bai; Chong Shen; Zhe Zhang; Zhouliang Wu; Yunkai Qie; Hailong Hu (Annals of Medicine)
Objective To explore the feasibility and efficacy of the modified technique of totally intracorporeal ileal conduit (IC) construction via vaginal approach following robot-assisted radical cystectomy (RARC) in females.Methods By comparing the perioperative outcomes of the modified technique with extracorporeal urinary diversion (ECUD), 31 females treated for bladder cancer with RARC and IC from May 2020 to December 2023 were retrospectively analyzed and divided into two groups: the ECUD group (10 patients) and the modified intracorporeal urinary diversion (MICUD group) (21 patients). The modified technique involved performing transvaginal natural orifice specimen extraction surgery (TV-NOSES) after RARC; followed by the transvaginal placement of an Endo-GIA stapler to manipulate the bowel for intracorporeal IC construction.Results Both groups’ surgeries were successfully completed by the same surgeon and team. Patients in the MICUD group had shorter total operative time, lower postoperative pain scores, quicker recovery, and shorter hospital stays. The learning curve of the MICUD showed two phases: a learning phase (cases 1-7) and a proficiency phase (cases 8-21). The incidence of postoperative complications between the two groups was similar. The mean follow-up times were 29.3 months (ECUD group) and 22.6 months (MICUD group). In the MICUD group, there was one case of local tumor recurrence, two cases of distant metastasis, including one death from progression; in the ECUD group, one patient had distant metastasis and died from progression.Conclusion RARC with MICUD represents a safe, feasible and easy-to-learn minimally invasive surgical approach. Patients experience less trauma and faster recoveries.